Pelaksanaan Program Kampus Mengajar Sebagai Strategi Peningkatan Mutu Pembelajaran Kecantikan Tata Rias - Deby Gemysa Faradiba; Mandalika; Fadli Ilham; Nurkemala Sari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Cosmetology beauty learning faces various complex problems including a lack of attention to improving the quality of human resources in the cosmetology field and a curriculum that is not yet fully relevant to industry needs. This problem will have an impact on reducing the quality of learning, motivation and student interest will be low. This research aims to improve the quality of beauty and cosmetology learning through campus teaching programs at SMK Negeri 2 Bukittinggi. This campus teaching program aims to empower students to help with the teaching process. This research applies qualitative methods with data collection techniques in the form of observations, interviews and literature studies regarding campus teaching programs on learning quality. The research results show that implementing campus teaching programs with innovative and interactive learning strategies and methods can improve the quality of beauty and cosmetology learning based on aspects of learning planning, learning processes, teacher competence, facilities and equipment, assessment and evaluation, and learning outcomes. Students also participate actively in learning, are more enthusiastic, and their motivation to learn increases. Students' interest in learning activities is because students are directly involved in the learning process, especially in make-up practice activities. The campus teaching program has had an impact on improving the quality of beauty and cosmetology learning at SMK Negeri 2 Bukittinggi.